EKSISTENSI MEDIA TRADISIONAL WAYANG ORANG SRIWEDARI SEBAGAI MEDIA INFORMASI PEMBANGUNAN DI ERA DIGITAL - Ardhi, Mahardika Kurnia; Wangi, Maya Sekar; Widiyowati, Estu (Solidaritas, 2024)
ABSTRACT The use of technological advances in the development of cultural values ​​contributes to the integration of digital technology and culture which will become a special attraction for the wider community. Culture has philosophy, artistic and moral values ​​as well as entertainment. Meanwhile, the aim of this author is to examine the existence of the traditional media Wayang Orang Sriwedari as a development information medium in the digital era? The aim of this research is to examine the existence of the traditional media Wayang Orang Sriwedari as a development information medium in the digital era. This type of research uses qualitative descriptive research while data collection techniques use interviews, observation and documentation. Data sources use written reports, photos, documentation, field observations and websites. The results of research on wayang orang as a performing art that conveys values ​​in a symbolic, connotative and aesthetic form by conveying the message of rules, norms and life guidelines that are expected to be followed by the next generation as well as the existence of the traditional media of wayang orang Sriwedari as a medium for development information in the digital era so that continues to exist, strengthened by supporting factors, namely community appreciation, support from the government and innovation and creativity. In this way, it is a form of anticipation to introduce the younger generation so that later it can have an impact on the emergence of younger generations and consistent audience attendance. Keywords: Existence, Traditional Media, Sriwedari Wayang Orang